Pengaruh Lingkungan Wilayah dan Kompensasi Kerja terhadap Kinerja Karyawan : (Studi Kasus Pada Perhutani Legok Haji) - Nurul Aeni; Darmawan Yudhanegara (Fakultas Ekonomi Universitas 45 Surabaya, 2024)
A company is greatly affected by employee performance. Hence, the company tends to always make efforts to enhance employee performance in the hope of achieving the goals that have been set. This research aims to identify the impact between the work environment and rewards or compensation on employee work performance. Quantitative methods were used in this research and the data analysis technique used was Partial Least Square-Structural Equation Modeling (PLS-SEM) via SmartPLS software. Data was collected through a questionnaire, with a population and sample consisting of 32 Perhutani Legok Haji employee respondents. Data analysis and hypothesis testing using outer and inner models. The results of the analysis show that there is an impact between work atmosphere and rewards or work compensation which has a good influence on employee worker performance. Therefore, it is recommended for Perhutani leaders to improve the work environment and compensation so that they can optimize employee performance in order to meet the company's demands.